THE EFFECT OF USING YOUTUBE VIDEOS ON STUDENTS` ENGLISH-SPEAKING SKILL OF ENGLISH CAMP PARE AEC MAN 2 KUANTAN SINGINGI - Ikrar Lidya Safitri; Hadriana; Supriusman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nowadays students watch YouTube videos to improve their language skill. This research focused on students’ English-speaking skill especially in English camp PARE AEC MAN 2 Kuantan Singingi. The objective of this research was to investigate whether there was a significant effect of using YouTube videos on students’ English-speaking skill of English camp PARE AEC MAN 2 Kuantan Singingi. This research employed a quantitative quasi-experimental design. The sample of the research consisted of 36 students, including 18 students in experimental group and 18 students in control group. Data were collected through pre-test and post-test speaking assessment conducted in the form of debate activities. Students’ speaking skill were assessed using debate-based speaking assessment framework integrating Brown’s (2004) speaking components with the debate assessment aspects of manner, matter, and method. The results of the research indicated that YouTube videos were an effective medium for improving students’ English-speaking skill. The experimental group improved from 62.6 to 78.3, with gain a 15.7, while the control group improved from 63 to 71.8 with gain 8.8. The result of the independent sample t-test showed a significant difference between the two groups (Sig. = 0.000 < 0.05). Therefore, that the use of YouTube videos had a significant effect on students’ English-speaking skill of English camp PARE AEC MAN 2 Kuantan Singingi.